Infectious potential and circulation of SARS-CoV-2 in wild rats - Kevyn Beissat; Virginie Lattard; Evelyne Picard-Meyer; Ambre Fafournoux; Sionfoungo Daouda Soro; Alexandre Servat; Françoise Vincent-Hubert; Franck Boué; Nolan Chatron; Elodie Monchatre-Leroy; Marine Wasniewski (PLoS ONE, 2025)
Since the beginning of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic, a wide range of animal species (pets, mink…) have been naturally infected with this betacoronavirus. The emergence of new variants has increased the ability of SARS-CoV-2 to infect species that were not susceptible to the “original” SARS-CoV-2, such as mice and rats. This work attempted to evaluate the role of urban rats in the SARS-CoV-2 transmission by combining surveillance studies of rat populations in urban environments, in vivo experimental inoculation of SARS-CoV-2 and comparative viral-receptor interaction in silico analyses. We studied the circulation of SARS-CoV-2 in wild Rattus norvegicus (n = 401) captured in urban areas and sewage systems of several French cities. Except for 3 inconclusive samples (2/75 from Bordeaux and 1/261 from Lyon) none of the 353 sera tested showed anti-SARS-CoV-2 antibodies by microsphere immunoassay. However, the 3 inconclusive sera samples were negative by virus neutralisation assay. No SARS-CoV-2 viral RNA was detected in all lungs collected from the 401 captured urban brown rats. In complement, four rat groups (two wild-type colonies, Rattus norvegicus and Rattus rattus , and two laboratory strains, Sprague-Dawley and Wistar) were inoculated with the SARS-CoV-2 Omicron BA.5. At 4 days post-inoculation, no infectious viral particles were detected in the lungs and upper respiratory tract (URT) while viral RNA was detected at a low level only in the URT of all groups. In addition, seroconversion was observed 14 days after inoculation in the four groups. By molecular modelling, the Omicron BA.5 receptor binding domain (RBD) had lower affinities for Rattus norvegicus and Rattus rattus ACE2 than Homo sapiens ACE2. Based on these results the SARS-CoV-2 Omicron BA.5 was unable to infect laboratory and wild type rats. In addition, Rattus norvegicus collected for this study in different areas of France were not infected with SARS-CoV-2.